The Effect of Work Motivation, Work Environment, and Work Discipline On Employee Work Productivity At The H Residence Apartment East Jakarta - Tian Permana; Setiasih Setiasih; Ida Adhani (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Aim - This paper tries to determine the effect of work motivation, work environment and work discipline on employees work productivity at The H Residence Apartment, East Jakarta, either partially or simultaneously. Methodology/approach - It uses quantitative methods and collects data through questionnaires for 56 The H Residence Apartment employees in East Jakarta. The Slovin formula calculated the data with an error rate of (e) 5%, Classic Assumption Test, multiple linear regression analysis, the coefficient of determination (R2), t test, and F test. Findings – It was found that other variables outside the study explain 40.1%. Then the work motivation variable (X1) has a partial effect on the work productivity variable (Y), the work environment variable (X2) has a partial effect on work productivity (Y), and work discipline (X3) has a partial effect on work productivity (Y). Partially, the most influential variable is discipline, follwed by work environment, and work motivation.